Analysis of leakage paths in a revolving vane compressor - Ang, Shue Ni (2015)
Compressor is a crucial component in the refrigeration and air conditioning system. Revolving vane (RV) compressor is a relatively new refrigeration compressor which will be introduced in this study. Similar to other refrigeration compressors, the volumetric efficiency of RV compressor is mostly affected by mechanical losses and leakage. In order to enhance the performance of RV compressor, it is important to understand all the phenomena involved in the leakage flow and hence able to estimate the total mass flow rate across every leakage path in the compressor. In this paper, simulations were carried out with ANSYS FLUENT software programs to determine the leakage conditions in RV compressor. In order to ensure the accuracy of the results, calculation of the leakage flow in radial clearance was performed theoretically and comparison was made and discussed. In this study, the simulation result was proven to have good agreement with the theoretical predictions. Upon validate the result of radial clearance, this study continued with the analysis of endface clearance and vane gap leakage of this compressor. With the usage of current setup in ANSYS FLUENT software, leakage in these leakage paths could be predicted even if the designs of compressor are modified. It could help for the future development of RV compressor.